Citizenship and indigenous Australians changing conceptions and possibilities - Peterson, Nicolas; Sanders, Will 1956- (Cambridge University Press, 1998)
For most of Australia's colonial history Aborigines and Torres Strait Islanders have been denied full membership of Australian society. This book examines the history of indigenous peoples' citizenship status and asks, is it possible for indigenous Australians to be members of a common society on equal terms with others? Leading commentators from a range of disciplines examine historical conceptions of indigenous civil rights, consider issues arising from recent struggles for equality and consider possibilities for multicultural citizenship that recognise difference. Topics include self-determination, the 1967 referendum, resource development, whether Australian Aborigines and white Australians can belong, the international law context, and sovereignty. This book makes a crucial intervention in current debates by providing the context for understanding struggles over distinctive indigenous rights
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Geschichte 1788-1998; Aborigines; Citizenship / Australia; Aboriginal Australians / Legal status, laws, etc; Staatsbürger; Bürgerrecht; Australien; Aufsatzsammlung; Konferenzschrift